Macroeconomics - Dornbusch, Rudiger; Fischer, Stanley; Startz, Richard (New York : McGraw-Hill, 2011)
The 11th edition of macroeconomics is published 31 years after the first. We have been both amazed and flattered by the response our book has received over those years.
Introduction and national income accounting -- Growth, aggregate supply and demand and policy -- First models -- Behavioral foundations -- Big events, international adjustments, and advanced topics
Includes index.
Keywords: MACROECONOMICS